Combined oral and enema treatment with Pentasa (mesalazine) is superior to oral therapy alone in patients with extensive mild/moderate active ulcerative colitis: a randomised, double blind, placebo controlled study. Issue 7 (10th June 2005) - Marteau, P; Probert, C S; Lindgren, S; Gassul, M; Tan, T G; Dignass, A; Befrits, R; Midhagen, G; Rademaker, J; Foldager, M
Abstract : Background and aims: Oral aminosalicylates are well established in the treatment of active mild/moderate ulcerative colitis (UC) when the disease is extensive (that is, beyond the splenic flexure). The majority of clinical symptoms relate to disease activity in the distal part of the colon and therefore this study was designed to investigate if adding a mesalazine enema to oral mesalazine has additional benefit for patients with extensive mild/moderate active UC. Methods: A randomised double blind study was performed in 127 ambulatory patients. All received 4 g/day (twice daily dosing) oral mesalazine for eight weeks. During the initial four weeks, they additionally received an enema at bedtime containing 1 g of mesalazine or placebo. Disease activity was assessed using the ulcerative colitis disease activity index, with clinical and endoscopic signs at four and eight weeks. Results: Remission was obtained in 44% (95% confidence interval (CI) 31%, 58%) of the mesalazine enema group (Me) and in 34% (95% CI 21%, 49%) of the placebo enema group (Pl) at four weeks (p = 0.31) and in 64% (95% CI 50%, 76%) of the Me group versus 43% (95% CI 28%, 58%) of the Pl group at eight weeks (p = 0.03). Improvement was obtained in 89% (95% CI 78%, 96%) of the Me group versus 62% (95% CI 46%, 75%) of the Pl group at four weeks (p = 0.0008) and in 86% (95% CI 75%, 94%) of the Me group versus 68% (95% CI 53%, 81%) of the Pl group at eight weeks (p = 0.026). Conclusion: In patients with extensive mild/moderate active UC, the combination therapy is superior to oral therapy. It is safe, well accepted, and may be regarded as firstline treatment.